Validação da escala de equilíbrio avançada de fullerton para pessoas com sequela de acidente vascular encefálico (AVE) - Santos, Larissa da Silva (2017)
The objective of study was to evaluate the reliability and validity of the Brazilian version of the Fullerton Advanced Balance Scale (FAB) in individuals with stroke. This is a methodological study addressing the validation of health measurement instrument. The steps of translation and validation were in accordance with the instructions of the Consensus based Standards for the selection of health status Measurement INstruments (COSMIN) and the Guidelines for Reporting Reliability and Agreement Studies (GRRAS). The test-retest and inter-rater reliability were evaluated by the Intraclass Correlation Coefficient (ICC). The Validity was assessed by the Pearson’s coefficient (r). Participants were 12 hemiparetic individuals, 61,58 years (±13,19). The test-retest and inter-rater reliability presented highly significant concordance (p<0.000) with excellent ICC= 0.990 for inter-rater, ICC= 0.987 rater 1 test-retest and ICC=0.985 rater 2 test-retest. The validation of construct of the Brazilian version of FAB with the MiniBESTest was high/excellent (r= 0,887) p<0,000. The discriminant validity was tested with the scores of gross dexterity of hemiparetic upper extremity using the Box and Blocks Test and the FAB Brazilian version, as expected, was a very low correlation (r= -0,049), p>0,05 ou p= 0,88. The Brazilian version of the Fullerton Advanced Balance scale (FAB) is a static and dynamic balance assessment that can be used in individuals with stroke. The FAB Brazilian version had excellent reliability, response stability and a construct validity that is in agreement with the English original scale.